Pengendalian Kualitas Produk Dan Risiko Produksi Jus Buah dengan Pendekatan Total Quality Management di King Juice Farhan - Veralianta Br. Sebayang; Irawati Lukman; Rizki Okina Putri; Alifa Fauzia Siswoyo; Fazar Hidayatulloh; Eka Yudha Firmansyah; Thoifatul Munawwaroh (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2024)
The fruit juice processing business, as part of the agroindustry sector, faces a range of challenges in maintaining product quality and managing production risks. These challenges mainly arise from the perishable nature of raw materials, inconsistent supply availability, and the relatively short shelf life of the final products. Such conditions create uncertainty that can affect both production consistency and the quality of the output. This study aims to examine how Total Quality Management (TQM) is implemented in controlling product quality, while also identifying the level of production risk at King Juice Farhan. A mixed methods approach was employed, combining both qualitative and quantitative analyses. Data were collected through direct observation, interviews, and questionnaires involving 11 informants, including the business owner and employees, selected using purposive sampling. The TQM analysis was conducted by assessing the contribution of ten key elements, while production risk was measured using standard deviation, coefficient of variation (CV), and the lower production limit. The findings indicate that the implementation of TQM falls into a good category, with a total contribution score of 90.79%. Among the elements, a strong focus on quality showed the highest contribution, reflecting a significant emphasis on product quality. In contrast, education and training, as well as employee involvement and empowerment, recorded the lowest contributions, suggesting limitations in human resource development. The level of production risk was classified as low, as indicated by a coefficient of variation of 0.04 and a stable lower production limit. Overall, the application of TQM has been effective in supporting quality control and reducing production variability. However, further improvements are still needed, particularly in strengthening human resource development and ensuring continuous, systematic improvement efforts.